Learning English through Literary Works - Afandi, Mujad Didien; Muflihah, Tatik; Aquariza, Novi Rahmania; Machmudah, Machmudah (Indonesia Berdaya, 2022)
Background. The lack of awareness and knowledge possessed by English teachers about the importance of literary works in learning English in elementary schools is a significant factor that makes English learning does not runs optimally. Therefore, this community service program (PKM) needs to be carried out to help students at one of MI (Islamic Elementary School) in Pranti village, Sidoarjo learn English effectively through literary works in the form of fairy tales. Method. The implementation of this program was divided into three stages, namely planning, implementation, and evaluation. At the planning stage, location survey and preliminary observation were conducted to get an overview of the partners. The team also discussed the problems experienced by the school and offered solutions. The implementation stage was carried out by conducting dissemination on learning English through literary works and implementation of English language learning through literary works. This program involved 25 third graders of the MI. Results. The result of the pretest revealed that all of the students (25 students) had unsatisfying scores.  After the implementation, the scores increased. All of the students (100%) achieved satisfying scores. The pretest and posttest scores showed a significantly different result as evidenced by the N-Gain score of 0.72 (72.2%). Conclusion. The community service program reveals that literary works in the form of fairy tales involved in classroom English learning through a short movie and flashcards is fairly effective to help the students learn English, especially in mastering the vocabulary. Abstrak: Kurangnya kesadaran dan pengetahuan yang dimiliki oleh guru bahasa Inggris akan pentingnya karya sastra dalam pembelajaran bahasa Inggris di sekolah dasar menjadi faktor signifikan yang menyebabkan pembelajaran bahasa Inggris menjadi kurang maksimal.Oleh karena itu, program pengabdian kepada masyarakat (PKM) ini perlu dilakukan untuk membantu siswa di salah satu MI (Madrasah Ibtidaiyah) di Desa Pranti, Sidoarjo mempelajari bahasa Inggris secara efektif melaui karya sastra yang berbentuk cerita dongeng. Metode. Pelaksanaan program ini dibagi dalam tiga tahapan, yaitu perencanaan, pelaksanaan, dan evaluasi.  Pada tahap perencanaan, survei lokasi dan observasi awal dilakukan untuk mendapatkan gambaran dari mitra. Tim ini juga mendiskusikan masalah yang dialami oleh sekolah tersebut serta menawarkan solusinya. Tahap pelaksanaan berisi kegiatan diseminasi tentang pembelajaran bahasa Inggris melalui karya sastra (berupa cerita dongeng), implementasi pembelajaran bahasa Inggris melalui karya sastra, monitoring dan bimbingan tentang penggunaan karya sastra dalam pembelajaran bahasa Inggris. Pada tahap terakhir, evaluasi pelaksanaan program dan keberlanjutan program setelah kegiatan PKM selesai. Program ini melibatkan 25 siswa kelas 3 di MI tersebut Hasil. Hasil pretes mengungkapkan bahwa semua siswa (100%) menghasilkan nilai yang tidak memuaskan. Setelah implementasi, nilai mereka meningkat. Semua siswa memperoleh nilai yang memuaskan. Nilai pretes dan posttes menunjukkan perbedaan signifikan yang dibuktikan dengan nilai N-Gain sebesar 0,72 (72,2%). Kesimpulan. Program PKM ini mengungkapkan bahwa karya sastra dalam bentuk cerita dongeng yang dilibatkan dalam pembelajaran bahasa Inggris di kelas melalui film pendek dan flashcards cukup efektif membantu siswa dalam mempelajari bahasa Inggris, khususnya dalam penguasaan kosakata